Application of AAV1 for Anterograde Transsynaptic Circuit Mapping and Input‐Dependent Neuronal Cataloging. Issue 1 (19th January 2022) - Zingg, Brian; Dong, Hong‐Wei; Tao, Huizhong Whit; Zhang, Li I.
Abstract: Viruses that spread transsynaptically provide a powerful means to study interconnected circuits in the brain. Here we describe the use of adeno‐associated virus, serotype 1 (AAV1), as a tool to achieve robust, anterograde transsynaptic spread in a variety of unidirectional pathways. A protocol for performing intracranial AAV1 injections in mice is presented, along with additional guidance for planning experiments, sourcing materials, and optimizing the approach to achieve the most successful outcomes. By following the methods presented here, researchers will be able to reveal postsynaptically connected neurons downstream of a given AAV1 injection site and access these input‐defined cells for subsequent mapping, recording, and manipulation to characterize their anatomical and functional properties. © 2022 Wiley Periodicals LLC. Basic Protocol : Stereotaxic injection of AAV1 for anterograde transsynaptic spread